Filosofi Jenang Procot sebagai Makanan Khas Upacara Tingkeban Masyarakat Suku Jawa - Sekar Kirana Wulandari; Lestari, Asti; Nadila Putri Budi Sugiarti; Siti Komariah; Mirna Nur Alia Abdullah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Jenang procot or procot porridge is one of the typical foods served during the tingkeban ceremony. Jenang procot is an important dish in the tingkeban ceremony because it symbolizes the parents' hopes for the smooth birth of the unborn baby. The tingkeban ceremony is usually held when the mother's pregnancy reaches seven months. The Javanese community believes that the tingkeban ceremony can provide ease for both the mother and the unborn child, from pregnancy to childbirth and until the child reaches adulthood. This research aims to explore the philosophy of jenang procot in the tingkeban ceremony of the Javanese community. The research employs Symbolic Interactionism Theory. The research method used is descriptive method, and data collection techniques involve literature study. The results show that the term 'jenang procot' comes from the Javanese language dictionary, meaning porridge as a request for the baby to be born smoothly. The research also indicates that jenang procot is an essential dish in the tingkeban ceremony because the Javanese community believes it is one way to prevent death during childbirth.